A Comprehensive Review of Denial of Service Attacks in Blockchain Ecosystem and Open Challenges - Rajasekhar Chaganti; Rajendra V. Boppana; Vinayakumar Ravi; Kashif Munir; Mubarak Almutairi; Furqan Rustam; Ernesto Lee; Imran Ashraf (IEEE Access)
With the proliferation of the blockchain technology ecosystems such as mining pools, crypto exchanges, full Bitcoin nodes, wallets, and pool protocol servers in recent years, the denial of service (DoS) attack vector has become more prevalent, and the attacks are targeted to the peer-to-peer networks and blockchain users. Despite blockchain enhancing security with decentralized design, secured distributed storage, and privacy, it is still vulnerable to new attack threats. If an attempted DoS is successful on blockchain, the impact is most likely massive given the fact that it is predominantly used for finance applications. An extensive account of the current state-of-the-art for possible DoS and corresponding mitigation techniques is not discussed in the existing research. This paper analyzes and categorizes the existing state-of-the-art DoS attack methods, detection techniques, and mitigation solutions targeting blockchain peer-to-peer networks as well as conventional network crypto exchanges. The review of the prior research shows that the blockchain ecosystem can be a target to successfully perform DoS attacks in the future, and technological advancements in blockchain are needed to mitigate potential attacks.